KARAKTERISTIK CERPEN-CERPEN CYBER - Kusmarwanti Kusmarwanti (LITERA, 2010)
This research study aims to describe the characteristics of the site that includes short stories cyber, the fact of short stories cyber namely plot, character, and setting, and the characteristics of the reader and the author of short stories cyber.The research subjects were short stories cyber in www.kolomkita.com dan  www.kemudian.com that published in April 2008. The data collected through data cards and analyzed by categorizing them in accordance with the predetermined categories.The research finding show that the site that contains short stories cyber determined by its organizer, both vision and personal as admin. Second, sitesthat contain short stories have hardly any cyber script selection process so that cyber short story has some weakness on the resolution of the story, the cultivation of the conflict, climax,character, and setting. A lot of short stories cyber are unfinished and very short. The shortstories writer and reader cyber is a community that found a path from them, by them, andfor them.